1997
DOI: 10.1002/etc.5620161119
|View full text |Cite
|
Sign up to set email alerts
|

Remobilization and export of cadmium from lake sediments by emerging insects

Abstract: Abstract-Emerging insects including, Diptera, Odonata, Ephemeroptera, and Trichoptera were collected from Lake 382 (L382) in 1991 and 1992 to estimate quantitatively the export of Cd by aquatic insects from a natural system having elevated Cd concentrations in the water and sediment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…To our knowledge, the values for adult midges are comparable to, or even lower than, cadmium levels in chironomid imagoes present in nonpolluted environments or habitats containing the same background levels as the reference sites in the present study [18,34]. However, these elevated levels dropped to background body burdens in adult midges.…”
Section: Shedding Of Accumulated Metalssupporting
confidence: 54%
“…To our knowledge, the values for adult midges are comparable to, or even lower than, cadmium levels in chironomid imagoes present in nonpolluted environments or habitats containing the same background levels as the reference sites in the present study [18,34]. However, these elevated levels dropped to background body burdens in adult midges.…”
Section: Shedding Of Accumulated Metalssupporting
confidence: 54%
“…However, these elevated levels dropped to background body burdens in adult midges. To our knowledge, the values for adult midges are comparable to, or even lower than, cadmium levels in chironomid imagoes present in nonpolluted environments or habitats containing the same background levels as the reference sites in the present study (Timmermans & Walker 1989;Currie et al 1997). However, when Timmermans & Walker (1989) exposed C. riparius larvae from a reference laboratory culture for only ten days to the same cadmium concentration as measured at the PI location, larval body burdens were comparable with those in the present study, whereas the imagoes showed a hundred-fold increase in cadmium body burdens.…”
Section: Shedding Of Accumulated Metalsmentioning
confidence: 81%
“…Our results are the first evidence that aquatic contaminants can drastically reduce both resource and contaminant flux to terrestrial food webs across a regional gradient. Aquatic systems are increasingly viewed as sources of contaminants to riparian food webs with emerging aquatic insects acting as vectors of contaminant transport (Currie et al 1997, Walters et al 2008). Yet we and others find that the impacts of aquatic metals on riparian consumers are dominated by a loss of resource subsidies (in this case aquatic dipterans) rather than changes in either contaminant exposure or flux (this study, Paetzold et al 2011).…”
Section: Discussionmentioning
confidence: 99%